Design of longitudinal finned tubes adjusted with the Cesàro curve (2018)
This paper proposes a process of higher heat transfer efficiency, through a fractal design over Cesàro curve as an extend surface for an exchange tube. Our designs yielded better results applying finite element analysis compared with the smooth surface commonly used in the industry. This new adaptation can be oriented toward applications involving gases and viscous liquids, for devices such as motors, boilers and dissipaters, among others.